Identificação e caracterização da expressividade de vendedoras de planos de saúde no momento da negociação - Souza, Claudia Célia Lopes (2007)
Introduction: The high competitiveness in the work market has demanded a good communication competence from those professionals who wish to have success in their careers. This is the reality of the salesperson, a voice-dependent professional, who needs to communicate efficiently in order to persuade the customer to buy. Knowing the use salespeople make their expressiveness was the focus of this study. Objective: To characterize the expressiveness of health service plan salespeople at the moment of a transaction according to the evaluation of a specialized speech therapist and the opinion of potential clients. Method: The subjects of this study are four health service plan salespeople who were audio-recorded at a simulated sales transaction. In the simulation researchers used a fake customer who was oriented and trained in advance and who fit the profile of a health service plan buyer. The recording was analyzed by a group of 31 potential clients and by a speech therapist specialized in the area. The specialist evaluated the health service salespeople at the moment of a transaction describing her findings in relation to the visual analysis, the oral expressiveness analysis, and the integration of body and voice for each topic considered by the salespeople, concluding with her personal judgment of the best and the worst salespersons. The 31 potential clients who helped with this study also made their judgments of the salespeople, and their opinions about them were categorized into cognitive, emotional and communicative aspects. Results: The results showed the non-verbal aspects of communication, like gestures, posture and good appearance were the most mentioned by the potential customers. For this group V1 (Salesperson 1) and V 4 (Salesperson 4) were considered the best salespeople and V2 (Salesperson 2) was the worst. The speech therapist considered V2 the best, and V3 (Salesperson 3) was considered the worst in the specialist s opinion. Conclusion: The results lead us to conclude that the non-verbal communication was the one that called the attention of the potential clients the most. In such evaluation, the first impression counted the most. In the case of this group, who could actually be real customers, there was not a deep analysis of communication, but just an idea, positive or negative, caused by the first impression. In this case, the gesture, the posture and the facial expressions had a very strong influence. In relation to this first impression, the speech therapist s opinion did not differ from that of the group. However, after deeper analysis, she selects as the best salesperson the one who, in spite of the excessive use of gestures, presented the most pertinent arguments, varied use of expressive resources, and showed more naturalness. On the other hand, the worst salesperson, in the speech therapist s point of view, was the one who didn t make use of argumentation, paused too many times, making the discourse non fluent and demanding too much attention from the listener in order to understand the message